U5 The 2013–14 european collaborative clinical group (ECCG) report on the european management of the partner notification guideline. (18th May 2015) - Ahmed, Sabah; Etomi, Omome; Brooks, Ben; Evans, Ceri; Tiplica, George-Sorin; Gomberg, Mikhail; Nandwani, Rak; Clarke, Emily; Patel, Raj
Abstract : Background/introduction: Partner notification (PN) is a public health service in which sexual partners of individuals with sexually transmitted infections (STI's) are informed of their exposure and offered testing, treatment, and support services. Previously there has been considerable variation in PN across Europe due to a number of factors including lack of financial resources and variations in look back periods. In 2013 the European guideline on PN was published in an attempt to bring consistency across the European region. Aim(s)/objectives: To evaluate the current PN policies amongst sexual health physicians across Europe against the current European guidelines. Methods: A clinical scenario based questionnaire was developed by a panel of European experts on PN, and this was disseminated to a group of 120 sexual health physicians across 38 countries, who are members of the ECCG – a network of sexual health specialists who conduct questionnaire-based research across the European region. Results: Provisional results demonstrate wide variation in PN across Europe, with differing legal and clinical requirements. Full results will be available by the conference. Discussion/conclusion: Partner notification varies widely across Europe and is not always in line with current European guidelines. There is a need for on going Europe wide education to ensure that PN occurs and is effective to avoid reinfection of the index case, and to prevent onwards transmission of STI's, especially in an environment of rising STI rates and increased travel of people within Europe.